Funding as an Element of Enterprise Project Management System (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article is devoted to research funding as an element of enterprise project management system. The study proved the importance of enterprise projects funding and placed the budgeting in the process of project planning. The complex analysis of the main components of the funding process was conducted. The recommendations to budgeting optimization were elaborated. A typical list of expenditure and necessary resources was presented, the most optimal way to display them in different types of reporting was identified. The criteria of evaluation of the accuracy of budgeting project were elaborated. Recommendations to improve project financial report were suggested. Elaborated suggestions will enable to increase the competitiveness of domestic enterprises and provide them with targeted development in the long term by enhancing project activity.